Knee injury and osteoarthritis outcome score (KOOS): Validity and reliability of an Indonesian version - Agustyaningsih, Nur Afni; Komalasari, Dwi Rosella (Malahayati International Journal of Nursing and Health Science, 2024)
Background: One of the health problems that often occurs in old age is musculoskeletal disorder, especially osteoarthritis which is a disorder of the joint cartilage. Knee injury and osteoarthritis outcome score is one of the measuring tools uses to access the function of patient with knee injuries and knee osteoarthritis.Purpose: To determine the cross-cultural adaption of modifications to the Indonesia version of the knee injury and osteoarthritis outcome score questionnaire by conducting validity and reliability tests.Method: This research was conducted in September 2023 at RSUI Kustati and RS UNS with a sample size of 55 participant. Sampling was carried out using purposive sampling technique. The KOOS instrument was given 2 times with an interval of 2 weeks.Results: The test-retest reliability result of the Indonesia version of the KOOS instrument between the two measurement sessions were very good (ICC 0.965, p<0.001, and 95% CI: 0.939-0.979). Internal consistency was confirmed to be very good with the Cronbach’s alpha test of 0.974.Conclusion: Based on the content validity result shown, there are 39 items with corrected correlation item values above 0.3 the conclusion was the Indonesia version of the KOOS instrument declaring reliable, but the content validity of the 2 items needs to be re-examined.